(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The study aims to demonstrate the civil liability for breach of the obligation to inform before the electronic contracting, which is considered the necessary tool to protect the consumer and enable him to express his will properly. The obligation to inform in electronic contracts is considered a legal guarantee to achieve equality between the parties to the contractual relationship as a result of cooperation between them. The study reached several conclusions, the most important of which is that the obligation to inform is considered a legal tool to protect the consumer from exposure to legal problems after the conclusion of the electronic contract. In the light of the findings of the study, it concluded with several recommendations, the most important of which is the necessity of developing a special system for informing the consumer, especially in light of smart robots, in the pre-contracting phase due to its privacy, in addition to tightening the penalty in case the producer or supplier breaches the obligation to inform, by imposing Punitive compensation in addition to compensation for damage.